QUALITY OF EMPLOYEE SERVICE IN ISSUING CERTIFICATES OF INCOME INCOMPETENCE (SKTM) IN CEMARA VILLAGE, LUBUK PAKAM DISTRICT - Dami Amando Sihotang; Maksum Syahri Lubis; Warjio Warjio (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Public service is one of the main functions of the government in meeting the needs of the community. One form of administrative service provided by the sub-district government is the issuance of a Certificate of Poverty (SKTM). This study aims to determine the quality of employee service in the issuance of SKTM in Cemara Sub-district, Lubuk Pakam District. This study uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The theory used in this study is Zeithaml's service quality theory, which includes five dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The results of the study indicate that the quality of service in the issuance of SKTM in Cemara Village is not yet optimal. This can be seen from the limited service facilities, the need to improve employee capabilities, and the lack of service support facilities. Therefore, efforts to improve service quality are needed so that the community can obtain better and more satisfactory services.